Frontier luminous strategy of functional silica nanohybrids in sensing and bioimaging: From ACQ to AIE. Issue 1 (10th September 2021) - Xu, Lijie; Jiang, Xiaoping; Liang, Kang; Gao, Meng; Kong, Biao
Abstract: Fluorescent silica organic–inorganic nanohybrids which combine designable luminescence performance of organic fluorescent dyes and various outstanding advantages of silica nanomaterials have attracted increasing research interests in these fascinating areas. Optical transparency and facile functional modification properties of silica material provide great opportunities to integrate desired fluorescent molecules for various frontier luminous applications. However, conventional organic dyes are typically subject to aggregation‐caused quenching due to their aggregation in silica matrix, which could be detrimental for their performance in sensing and biomedical applications. The appearance of aggregation‐induced emission luminogens (AIEgens) paves a new way for developing highly efficient fluorescent silica nanohybrids (FSNs). FSNs with intensive luminescence could be obtained due to the formation of aggregates and the restricted intramolecular motion of AIEgens in silica inorganic matrix. In this review, the reported fabrication methodologies of various FSNs based on colloidal silica nanoparticles (SNs) and mesoporous SNs including physical entrapment and covalent strategies are summarized. Especially, the AIEgens‐functionalized silica hybrid nanomaterials are introduced in detail. Furthermore, chemical sensing, biosensing, and bioimaging applications of resultant FSNs are also discussed. Abstract : As a novel multifunctional material, fluorescent silica organic–inorganic nanohybrids (FSNs) have been widely applied in sensing and biomedical applications. AIE luminogens (AIEgens) with tunable color have been introduced in silica nanoparticles to develop ultra‐bright FSNs. AIEgens‐functionalized FSN materials will play a potentially great value in prospective practical applications with further design and optimization.